The effect of repetitive rugby scrummaging on force output and muscle activity - Cochrane, D. J.; Harnett, K.; Lopez-Villalobos, N.; Hapeta, J. (Sports Medicine International Open, 2017)
During rugby scrummaging, front row forwards encounter high levels of force that has been suggested to cause transient fatigue and is likely to reduce subsequent performance. However, little is known about the effect of repetitive scrummaging on force output and onset of fatigue. Twelve male front row forwards (21.5±2.3 yr; height 185.7±4.4 cm; body mass 108.5±7.1 kg) each performed three sets of five maximal-effort isometric scrums for 10?s, with 40?s rest separating each repetition; 2?min recovery was provided between each set. Force output and electromyography (EMG) of the right medial gastrocnemius (MG), biceps femoris (BF), gluteus maximus (GM), erector spinae (ES), rectus abdominis (RA), external oblique (EO), internal oblique (IO), and rectus femoris (RF) were assessed. There was no significant force decrement from performing 15 scrums and no fatigue was detected from EMG median frequency and mean amplitude. For training and practice purposes, coaches and trainers can be confident that 15 individual repetitive static scrums against a machine are unlikely to cause a reduction in force production and promote fatigue. However, the effect of rugby-related activities in conjunction with scrummaging requires further research to determine if transient fatigue is causal to scrummaging for subsequent performance.